ETS-10 as a photocatalyst. (2003) - Krisnandi, Yuni K.; Southon, Peter D.; Adesina, Asoji A.; Howe, Russell F.
Abstract : ETS-10 is a microporous titanosilicate zeolite with a framework containing linear Ti- O -Ti- O- chains. This paper describes an investigation of the photoreactivity of ETS-10 with the particular objective of evaluating the potential of this novel material as a zeolitic photocatalyst. The photoreactivity and photocatalytic activity of ETS-10 are strongly influenced by defects in the structure. A relatively defect free material catalyses photo-polymerisation of ethene, and in the presence of oxygen catalyses the partial oxidation of ethene to acetic acid and acetaldehyde, which remain strongly adsorbed in the pores. A more defective material is photoreduced when irradiated in the presence of adsorbed ethene, and catalyses the complete oxidation of ethene to carbon dioxide and water in the presence of oxygen. These differences are attributed to differences in the concentrations of exposed titanium sites associated with defects in the ETS-10 structure.